Bridging Nutritional Gaps In Diabetes Care: Evaluating The Benefits Of Diabetes Specific Protein Supplements (DSPS) In Blood Sugar Management And Health Outcomes Perceived By Indian Type 2 Diabetes Patients - Padmanabh, Pushkala; Karkera, Priya (South Eastern European Journal of Public Health, 2025)
Background: Diabetes mellitus (DM) is a growing global health challenge, with Type 2 DM accounting for a significant disease burden. Effective management strategies, including diet and lifestyle modifications, are critical to reducing the complications associated with diabetes. However, many individuals, particularly in India, do not consume sufficient protein and fibre through their diet, highlighting the need for targeted nutritional interventions. Diabetes-specific protein supplements (DSPS), formulated with high-quality proteins, fibre, essential vitamins, and minerals, have emerged as a potential solution. Objective: This self-reported experience aimed to assess the level of satisfaction and perceived health benefits among individuals with diabetes who consumed a DSPS for one month as part of their diabetes management routine. Methods: A Phase 4 post marketing survey was conducted across six cities in India with 500 participants identified by healthcare professionals as needing additional protein and fibre in their diets. Participants consumed the DSPS [Protinex Diabetes Care] daily for one month. Surveys conducted before and after consumption assessed satisfaction and perceived benefits, including blood sugar management, energy levels, physical strength, and product attributes (e.g., taste, miscibility, and ease of use). Data were analyzed using SPSS 24.0, employing descriptive and inferential statistics. Results: Of the 500 participants, 480 completed the survey. The majority (99.4%) appreciated the taste of DSPS, 92.5% found it easy to mix, and 98.3% successfully incorporated it into their routines. A significant proportion perceived positive benefits: 82% experienced enhanced blood sugar control, 92.5% perceived increased energy levels, 80% felt satiated throughout the day, and 78.8% reported improved physical strength. Additionally, 72% reported positive experiences in terms of fewer blood sugar spikes, and 76% experienced reduced mood swings. Notably, 98.8% expressed willingness to recommend DSPS to others. Conclusion: This survey suggests that DSPS may potentially offer positive results based on self-reported user experience such as improved glycaemic control, reduced fatigue, enhanced physical strength, and better appetite management. Due to the limitation of such self-reported survey of user experience, and the absence of a control group, no causal inferences can be made. Further research is needed to confirm the benefit of DSPS.